2010
DOI: 10.1016/j.mce.2010.07.006
|View full text |Cite
|
Sign up to set email alerts
|

A factor(s) secreted from MIN-6 β-cells stimulates differentiation of definitive endoderm enriched embryonic stem cells towards a pancreatic lineage

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. A c c e p t e d M a n u s c r i p t 2 AbstractIn t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Its expression seems likely to be very important in the in vitro differentiation of ES cells along pancreatic cell lineages (Miyazaki et al ., ). The previous reports by other investigators suggested that ES cells cultivated with pancreatic rudiments, mesenchyme (Shiraki et al ., ) or MIN‐6 β ‐cell‐conditioned medium could express Hnf1 β , PDX‐1 and Ptf1 (Uroic et al ., ). The genes tested here ( PDX1 , INS‐1 and INS‐2 ) did not show a concentration‐dependent increase in expression levels (Figure A).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Its expression seems likely to be very important in the in vitro differentiation of ES cells along pancreatic cell lineages (Miyazaki et al ., ). The previous reports by other investigators suggested that ES cells cultivated with pancreatic rudiments, mesenchyme (Shiraki et al ., ) or MIN‐6 β ‐cell‐conditioned medium could express Hnf1 β , PDX‐1 and Ptf1 (Uroic et al ., ). The genes tested here ( PDX1 , INS‐1 and INS‐2 ) did not show a concentration‐dependent increase in expression levels (Figure A).…”
Section: Discussionmentioning
confidence: 97%
“…() reported that rat islet endothelium‐conditioned culture medium (ECCM) supports pancreatic β cell function; interestingly, both insulin release and total insulin content were increased in the islets cultured in ECCM. Mouse ES cells were cultured using MIN‐6 β cell conditioned medium; the data indicated that MIN‐6 β cells secreted factors that promoted differentiation of mouse ES cells towards a pancreatic fate (Uroic et al ., ). Talavera‐Adame et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simply elevating the culture above the gas impermeable surface and allowing for mass transfer on both the basal and apical surface of the tissue improves the oxygen profiles. The apical surface is covered by a minimal height of culture medium reducing oxygen mass transfer distances but requiring frequent changes to prevent tissue drying due to evaporative loss (Bigas et al, 1995;Uroic et al, 2010).…”
Section: Culture On Liquid Permeable Transwell Devicesmentioning
confidence: 99%